2017
DOI: 10.1111/ppl.12651
|View full text |Cite
|
Sign up to set email alerts
|

A novel cotton WRKY gene, GhWRKY6‐like, improves salt tolerance by activating the ABA signaling pathway and scavenging of reactive oxygen species

Abstract: WRKY transcription factors are transcriptional regulators of signaling pathways involved in biotic and abiotic stress responses. In this study, we report that ectopic expression of the GhWRKY6-like gene significantly improved salt tolerance in Arabidopsis thaliana while silencing the GhWRKY6-like increase the sensitivity to abiotic stresses in cotton. GhWRKY6-like was localized to the nucleus. Expression of GhWRKY6-like was remarkably induced by salt, polyethylene glycol (PEG) and abscisic acid (ABA) treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(82 citation statements)
references
References 63 publications
4
73
0
Order By: Relevance
“…Furthermore, our sequencing data indicated that two candidate genes encoding SOD, fifteen genes encoding POD and one gene encoding APX were obviously upregulated after the application of SA (Table S4). Considering that SOD, POD, and APX could function in the scavenging of ROS to improve salt tolerance [44], we speculated that moderate SA could mitigate the salt damage to cells by activating SOD, POD, and APX.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our sequencing data indicated that two candidate genes encoding SOD, fifteen genes encoding POD and one gene encoding APX were obviously upregulated after the application of SA (Table S4). Considering that SOD, POD, and APX could function in the scavenging of ROS to improve salt tolerance [44], we speculated that moderate SA could mitigate the salt damage to cells by activating SOD, POD, and APX.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was found in cotton, the expression of GhWRKY6‐like was remarkably induced by ABA (Ullah et al . ). Genes encoding heat shock transcription factors, GATA, HY5, B3 domain transcription factors and trihelix DNA binding transcription factors were also changed in their expression levels after ABA treatment.…”
Section: Discussionmentioning
confidence: 97%
“…In the Gh4CL7 gene-silenced plants, the H 2 O 2 content was found to be increased significantly under drought stress, so was the MDA level, an indicator of ROS destructive effects [40]. SOD, POD, and CAT are antioxidant enzymes in plant cells which scavenge the toxic ROS and lead to enhanced tolerance under stress conditions [41]. We found that the activities of SOD, POD, and CAT were lower in the TRV:Gh4CL7 plants than in the TRV:00 plants indicating that the reduced ability of the Gh4CL7 silenced plants to scavenge ROS that might have led to membrane damages and chlorophyll content reduction.…”
Section: Discussionmentioning
confidence: 99%